Strategi Memahami dan Mengimplementasikan Pendekatan Deep Learning untuk Meningkatkan Kualitas Pembelajaran di Tingkat SMPK Frater Maumere - Klemens Mere (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The Deep Learning approach is not merely a learning model that emphasizes cognitive mastery of material, but rather one that develops analytical, reflective, problem-solving, and creative abilities, as well as the skill to connect concepts with real-world situations. The purpose of this study is to understand and implement the deep learning approach to improve the quality of learning at SMPK Frater Maumere. This research employs a literature review method using a Systematic Literature Review (SLR) approach. This method was selected to obtain a comprehensive understanding of the strategies for interpreting and implementing the deep learning approach to enhance learning quality at the junior high school level, particularly in the context of SMPK Frater Maumere. Based on the analysis of literature using the Systematic Literature Review (SLR) method, it can be concluded that the application of the deep learning approach in junior high school education has significant potential to improve the quality of both the learning process and students’ learning outcomes.